A Study on Management of Premature Rupture of Membranes (PROM) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Premature rupture of membranes (PROM) is a common obstetric complication. Knowledge of etiopathogenesis, diagnosis, complications & management of PROM has increased due to extensive research in the recent past. Yet, there is no unanimous opinion regarding optimum management of PROM. The aim of the study was to observe the patients during labor and compare the latent period, duration of first stage of labor, modes of deliveries and the use of oxytocin and its outcome in PROM cases with controls.Materials and methods: In this study, the definition of PROM used is – rupture of fetal membranes before the onset of true labor pain. The minimum gestational age was taken to be 28 weeks. Diagnosis of PROM was mainly clinical. A cohort study was conducted in the Dept. of Obs & Gynae of KPL Medical College & Hospital, Kolkata on 100 cases of PROM and 100 cases of comparison group, over a period of one year.Results: It was observed that onset of labor was more rapid with increasing gestational age, use of oxytocin for induction & augmentation of labor & operative deliveries were higher in PROM cases.Conclusion: Individualized management of PROM cases depending on the gestational age and risk of complications is the best way to achieve a good feto-maternal outcome.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 94-98